PART A
The equation of the parabola in vertex form is given by the formula,
![y - k = a {(x - h)}^{2}](https://tex.z-dn.net/?f=y%20-%20k%20%3D%20a%20%7B%28x%20-%20h%29%7D%5E%7B2%7D%20)
where
![(h,k)=(1,-2)](https://tex.z-dn.net/?f=%28h%2Ck%29%3D%281%2C-2%29)
is the vertex of the parabola.
We substitute these values to obtain,
![y + 2 = a {(x - 1)}^{2}](https://tex.z-dn.net/?f=y%20%20%2B%202%20%3D%20a%20%7B%28x%20-%201%29%7D%5E%7B2%7D%20)
The point, (3,6) lies on the parabola.
It must therefore satisfy its equation.
![6 + 2 = a {(3 - 1)}^{2}](https://tex.z-dn.net/?f=6%20%20%2B%202%20%3D%20a%20%7B%283%20-%201%29%7D%5E%7B2%7D%20)
![8= a {(2)}^{2}](https://tex.z-dn.net/?f=8%3D%20a%20%7B%282%29%7D%5E%7B2%7D%20)
![8=4a](https://tex.z-dn.net/?f=8%3D4a)
![a = 2](https://tex.z-dn.net/?f=a%20%3D%202)
Hence the equation of the parabola in vertex form is
![y + 2 = 2 {(x - 1)}^{2}](https://tex.z-dn.net/?f=y%20%20%2B%202%20%3D%202%20%7B%28x%20-%201%29%7D%5E%7B2%7D%20)
PART B
To obtain the equation of the parabola in standard form, we expand the vertex form of the equation.
![y + 2 = 2{(x - 1)}^{2}](https://tex.z-dn.net/?f=y%20%20%2B%202%20%3D%202%7B%28x%20-%201%29%7D%5E%7B2%7D%20)
This implies that
![y + 2 = 2(x - 1)(x - 1)](https://tex.z-dn.net/?f=y%20%2B%202%20%3D%202%28x%20-%201%29%28x%20-%201%29)
We expand to obtain,
![y + 2 = 2( {x}^{2} - 2x + 1)](https://tex.z-dn.net/?f=y%20%2B%202%20%3D%202%28%20%7Bx%7D%5E%7B2%7D%20%20-%202x%20%2B%201%29)
This will give us,
![y + 2 = 2 {x}^{2} - 4x + 2](https://tex.z-dn.net/?f=y%20%2B%202%20%3D%202%20%7Bx%7D%5E%7B2%7D%20%20-%204x%20%2B%202)
![y = {x}^{2} - 4x](https://tex.z-dn.net/?f=y%20%3D%20%20%7Bx%7D%5E%7B2%7D%20%20-%204x)
This equation is now in the form,
![y = a {x}^{2} + bx + c](https://tex.z-dn.net/?f=y%20%3D%20a%20%7Bx%7D%5E%7B2%7D%20%20%2B%20bx%20%2B%20c)
where
![a=1,b=-4,c=0](https://tex.z-dn.net/?f=a%3D1%2Cb%3D-4%2Cc%3D0)
This is the standard form